Characteristics of MDS patients seen at private practices differ significantly from those treated at university hospitals in Germany - Nolte, Florian; Schumann, Christiane; Klein, Stefan; Reinwald, Mark; Hofmann, Wolf-Karsten (Journal of cancer research and clinical oncology, 2012)
Background: Myelodysplastic syndromes (MDS) are mainly a disease of the elderly. Commonly, MDS patients are treated in an outpatient setting making hematological/oncological private practices (PP) an important backbone in the management of MDS patients. Methods: To gain more insights into the characteristics of patients with MDS treated in hematological/oncological PP and to evaluate the daily diagnostic routines and classification systems used, we performed questionnaire-based analyses. Moreover, to investigate whether characteristics of MDS in PP differ from patients treated in specialized MDS centers in university hospitals (UH), we compared both cohorts of MDS patients.